Effect of different preparation approaches on Pt-Modified TiO2/g-C3N4 for effective photocatalytic degradation of RR4 dye under visible light - Azhar, Rahil; Jahari, Nurul Izzati; Roslan, Nurul Izzah; Mohamad Abdul Adzis, Nur Syamimi; Suhaimi, Nur Hidayatul Syazwani; Zanal, Nur Izzati Nabilah; Rosli, Mohamad Afiq; Abdul Manaf, Nor Azlian; Wan Ismail, Wan Izhan Nawawi (Universiti Teknologi MARA, Perlis, 2025)
This study investigates the effectiveness of TiO2/g-C3N4/Pt composites prepared under different methods for photocatalytic dye degradation in wastewater. Initially, the TiO2/g-C3N4 composite was prepared by dry and wet methods at different ratios. Both methods involved mixing P25 and g-C3N4, followed by calcination at 550 oC for 2 h with a heating rate of 5 o C/min in a tube furnace. To fabricate TiO2/g-C3N4/Pt, platinum (Pt) was deposited onto the TiO2/g-C3N4 wet composite using the photo deposition method. Reactive Red 4 (RR4) dyes were used as model pollutants to examine the photocatalytic activity of TiO2/g-C3N4/Pt. The structural, optical, and photoelectrochemical properties of this prepared sample TiO2/g-C3N4/Pt were further investigated in detail. Characterization was performed by X-ray diffraction (XRD), Fourier transform attenuated total reflectance (FTIR-ATR), and UV-vis diffuse reflectance spectroscopy (UV-Vis DRS). XRD analysis showed characteristic peaks at 13.2° and 27.3° for g-C3N4. In FTIR, functional groups present in TiO2/g-C3N4/Pt (TC-Pt) were observed for NH2 and OH around 3300 cm-1 to 3700 cm-1, C-N at 1650 cm-1, C=N at 1200 cm-1 and triazine ring at 801 cm-1. Based on UV-Vis Analysis, TC-Pt shows a more absorption edge toward visible light, indicating a reduced band gap from 2.80 eV to 1.6 eV. For PEC analysis, LSV, EIS, and CA demonstrated that TC-Pt has high current density under light, low charge transfer resistance under light, and high photocurrent response, respectively. For photocatalytic degradation, all modified samples degraded over 80% of RR4 dye within 1 h of light irradiation. Among the samples, TC-Pt with 1.5% Pt loading exhibits the highest degradation reaction rate constant with a value of 0.0708 min-1.